THE INFLUENCE OF STORY-BASED INSTRUCTIONAL VIDEOS ON STUDENTS' UNDERSTANDING OF PHYSICS CONCEPTS - Syamsul Fahmi (INERCYS: Institute of Educational, Research, and Community Service, 2026)
Story-based learning videos constitute an important aspect of physics education, as many students still perceive physics as a difficult and abstract subject, leading to low levels of conceptual understanding and learning motivation. This condition highlights the need for further research focusing on the use of innovative and engaging instructional media to enhance students’ comprehension of physics concepts. This study aims to examine the effect of story-based learning videos on students’ conceptual understanding in physics. The research employed a quantitative method with an experimental approach, using a quasi-experimental design in the form of a pretest–posttest control group design. Data were collected through conceptual understanding tests, observation sheets, and documentation, and were analyzed using descriptive statistics, an independent samples t-test, and N-gain analysis. The findings reveal that students in the experimental group showed a significant improvement in conceptual understanding, with the mean score increasing from 63.20 to 84.10 and an N-gain value of 0.72 (high category), while the control group achieved an N-gain of 0.41 (medium category). Furthermore, the t-test result yielded a significance value of 0.001 < 0.05, indicating a statistically significant difference between the two groups, thereby demonstrating that story-based learning videos are effective in improving students’ conceptual understanding in physics. This study provides a significant contribution to the advancement of physics education at both national and international levels through the integration of innovative multimedia-based learning approaches that enhance student engagement, conceptual understanding, and learning outcomes. In addition, the findings offer valuable insights into the application of storytelling techniques in science education as an effective pedagogical strategy and are expected to serve as a reference for future research, particularly in the areas of technology-enhanced learning and concept mastery, while encouraging more in-depth and applied studies in related fields.